Fostering Religious Tolerance in West Papua: A Case Study of Muhammadiyah's Higher-educational Institutions - Muhaiminah Akib; Rezkiah Hartanti; Hermanto Suaib (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2020)
This study aims to identify the role of Muhammadiyah's higher-educational institutions in fostering religious tolerance in West Papua. Applying the qualitative method, this research is conducted in three Muhammadiyah higher-educational institutions in West Papua i.e., Universitas Muhammadiyah Sorong (UM Sorong) Sorong City, Universitas Pendidikan Muhammadiyah Sorong (UNIMUDA) Sorong Regency, and Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Muhammadiyah Manokwari. The results showed that Muhammadiyah’s higher-educational institutions are inclusive in terms of spiritual understanding. In fostering religious tolerance there are three approaches taken by the three Muhammadiyah higher-educational institutions in West Papua: 1) social approach, 2) cultural approach, and 3) excellent service approaches. The strategies implemented the role includes: 1) disseminating Muhammadiyah’s vision and mission, 2) inculcating tolerance values since the beginning of students joining Muhammadiyah higher-educational institutions, 3) strengthening tolerance value by lecturing processes, conducting, sharing sessions both formally and informally, and 4) empowering student activity units and other facilities that support multicultural student interaction processes.